Using KASP technique to screen LRRK2 G2019S mutation in a large Tunisian cohort - Zied Landoulsi; Sawssan Benromdhan; Mouna Ben Djebara; Mariem Damak; Hamza Dallali; Rym Kefi; Sonia Abdelhak; Amina Gargouri-Berrechid; Chokri Mhiri; Riadh Gouider (BMC, 2017)
Abstract Background In North African populations, G2019S mutation in LRRK2 gene, encoding for the leucine-rich repeat kinase 2, is the most prevalent mutation linked to familial and sporadic Parkinson's disease (PD). Early detection of G2019S by fast genetic testing is very important to guide PD's diagnosis and support patients and their family caregivers for better management of their life according to disease's evolution. Methods In our study, a genetic PD's diagnosis tool was developed for large scale genotyping using Kompetitive Allele Specific PCR (KASP) technology. We investigated G2019S's frequency in 250 Tunisian PD patients and 218 controls. Results We found that 33.6% of patients and 1.3% of controls were carriers. Demographic characteristics of patients with G2019S had no differences compared with non-carrier patients. Thereby, we could emphasize the implication of G2019S in PD without any distinctive demographic factors in the studied cohort. Sixty patients out of 250 were genotyped using Taqman assay and Sanger sequencing. The genotyping results were found to be concordant with KASP assay. Conclusions The G2019S mutation frequency in our cohort was similar to that reported in previous studies. Comparing to Taqman assay and Sanger sequencing, KASP was shown to be a reliable, time and cost effective genotyping assay for routine G2019S screening in genetic testing laboratories.